Bibliometric analysis of consumer ethnocentrism and consumer racism with islamic elements - Abdul Latif, Samshul Amry; Mohd Ali, Afiza; Mohd Farudz, Baiduri Zaiyyanna; Dwi Putra, Halim (Penerbit UiTM, 2025)
This study examines consumer ethnocentrism and consumer racism literature with Islamic elements, employing bibliometric analysis through the Bibliometrix software to analyse current research trends and identify emerging themes. Retrieving 101 publications with 1,277 overall citations from the Scopus database, this study explores the structure and evolution of consumer ethnocentrism and consumer racism. Three bibliometric analyses were conducted, including citation analysis, co-citation analysis, and keyword co-occurrence analysis, to reveal past, present, and future research trajectories. The study identifies two significant research streams: the interplay between consumer ethnocentrism and cultural identity, and the impact of consumer racism on purchasing behaviour in Islamic markets. Additionally, the findings highlight the increasing global interest in consumer ethnocentrism and consumer racism with Islamic elements, with contributions from 35 countries including China, Canada, India, Turkey, and Indonesia, and underscore the need for high-quality research that addresses the complexities of consumer behaviour in diverse cultural contexts. This study contributes to the theoretical understanding of consumer ethnocentrism and consumer racism with Islamic elements, emphasizing the importance of quality over quantity in academic publications. It also suggests directions for future research to further explore the intersectionality of these concepts with broader social issues. As one of the first studies to apply bibliometric analysis to the fields of consumer ethnocentrism and consumer racism with Islamic elements, this research provides valuable insights into significant issues and emerging trends, paving the way for future scholarly inquiry.